Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1530-0277.2008.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Characteristics of Italian Children With Fetal Alcohol Spectrum Disorders

Abstract: Background-Children with fetal alcohol spectrum disorders (FASD) display many problems ranging from deficits in intelligence to behavioral difficulties. Thus, many studies have aimed to better define the neuropsychological characteristics of children with FASD. The current article describes the neuropsychological characteristics of Italian children with severe diagnosis within FASD and compares them with controls. It was expected that intellectual functioning, language comprehension, academic skills, and inatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 49 publications
2
52
1
1
Order By: Relevance
“…5,9 One approach used successfully to determine the minimal prevalence of FASD in communities in South Africa, [10][11][12][13][14] Italy, 15,16 and Croatia 17,18 uses active case ascertainment in schools. Providing targeted physical examinations and cognitive/ behavioral testing to primary school children [19][20][21][22] and interviewing their mothers [23][24][25] can be effective for studying FASD prevalence and characteristics.…”
mentioning
confidence: 99%
“…5,9 One approach used successfully to determine the minimal prevalence of FASD in communities in South Africa, [10][11][12][13][14] Italy, 15,16 and Croatia 17,18 uses active case ascertainment in schools. Providing targeted physical examinations and cognitive/ behavioral testing to primary school children [19][20][21][22] and interviewing their mothers [23][24][25] can be effective for studying FASD prevalence and characteristics.…”
mentioning
confidence: 99%
“…Analyzing the samples addressed in these studies, it was clear that mostly they consisted of milder forms of FASD or of individuals who had been exposed to alcohol, but without a diagnosis, as stated in several studies. 13,14,17,20,31,34,35,46,47 The fact that the samples presented predominantly milder forms of FASD resulted in higher scores. This explains why some studies state that most individuals who were prenatally exposed to alcohol are not intellectually impaired.…”
Section: General Intelligencementioning
confidence: 99%
“…11 However, one clinical sample of a high-quality study was classifi ed in the middle range, possibly due to environmental factors that favoured the cognitive development of children. 17 When the sampled individuals who were exposed to alcohol were compared with each other, it was found that those with FAS had greater impairment in terms of general, 16,27,31 as well as verbal and non-verbal intelligence. 13 which indicated the most severe form of the spectrum.…”
Section: General Intelligencementioning
confidence: 99%
See 2 more Smart Citations